2008
DOI: 10.1007/s10461-008-9404-2
|View full text |Cite
|
Sign up to set email alerts
|

Needle and Syringe Sharing Practices Among Injecting Drug Users in Tehran: A Comparison of Two Neighborhoods, One with and One Without a Needle and Syringe Program

Abstract: This study was conducted to compare needle and syringe sharing practices among injecting drug users (IDUs) in two neighborhoods, one with and one without a needle and syringe program (NSP). In 2005, 419 street-based IDUs were interviewed at specific locations in two neighborhoods where IDUs are known to congregate. We compared self-reported needle and syringe access and use between IDUs from a neighborhood with an active NSP to IDUs from a neighborhood without such an intervention. A significantly smaller prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 15 publications
3
27
1
Order By: Relevance
“…Few recent HIV test results complement the findings of other studies on PWID across the country indicating a relatively low rate of HIV testing among this population (Rahimi-Movaghar, et al, 2012;Rahnama, et al, 2014;Zamani, et al, 2010). For example, a study in the capital city of Tehran, Iran reported that only one-fourth of their participants had ever tested for HIV; 10.5% of whom had not received their test results (Rahnama, et al, 2014).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Few recent HIV test results complement the findings of other studies on PWID across the country indicating a relatively low rate of HIV testing among this population (Rahimi-Movaghar, et al, 2012;Rahnama, et al, 2014;Zamani, et al, 2010). For example, a study in the capital city of Tehran, Iran reported that only one-fourth of their participants had ever tested for HIV; 10.5% of whom had not received their test results (Rahnama, et al, 2014).…”
Section: Discussionsupporting
confidence: 62%
“…After piloting small-scaled harm reduction (HR) policies in certain seetings in Iran, the comprehensive HR programs commenced in 2002 and included opioid substitution treatment (OST), needle exchange programs (NEP), methadone maintenance therapy (MMT), PWID outreach programs, and triangular clinics (Malekinejad & Vazirian, 2012;Rahnama, et al, 2014;Razzaghi, et al, 2006;Zamani, et al, 2010). In Iran, the Ministry of Health (MOH), State Welfare Organization (SWO) and the Iranian Prison Organization (IPO) work in tandem in providing HR services (e.g., free HIV counselling and testing (HCT)) to key populations (e.g., PWID).…”
Section: Introductionmentioning
confidence: 99%
“…Over two-thirds of all new identified HIV cases have been attributed to unsafe injection (4,(6)(7)(8). To reduce the risk and harms associated with injections, needle and syringe programs (NSP) have been developed and implemented widely (9)(10)(11)(12). In Iran, NSP is the cornerstone of HIV prevention interventions and has been implemented in different community settings since 2002 (8,10,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the risk and harms associated with injections, needle and syringe programs (NSP) have been developed and implemented widely (9)(10)(11)(12). In Iran, NSP is the cornerstone of HIV prevention interventions and has been implemented in different community settings since 2002 (8,10,(13)(14)(15). NSP is being delivered through drop-in centers, (DIC) for those who have access to services and by outreach and second-hand exchanges (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Kerack is easier to prepare for injection and may cause withdrawal symptoms in shorter time intervals, meaning that kerack users tend to inject more frequently [15]. IDU in Iran also share needles, hand-made injecting instruments, and other drug paraphernalia in drug shooting venues and inside prisons [10,12,[15][16][17]. As a result, the conjunction of the twin epidemics of injecting drug use and HIV in Iran could prove devastating.…”
Section: Introductionmentioning
confidence: 99%